2023
DOI: 10.1007/s00383-023-05388-z
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent early complications of hypospadias repair: a single institutional experience

Abstract: Purpose To correlate age at hypospadias repair with early post-operative complications and highlight need for adaptation to post-operative care in older children. Methods Anecdotal evidence suggests boys with delayed surgery for hypospadias suffer increased rates of early post-operative complication. Hence, a retrospective analysis was conducted of all patients undergoing hypospadias repair between March 2019 and 2022. Results Ninety eight pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Because hypospadias impacts children psychologically and developmentally, the recommended age for surgery is 6 to 18 months. 7 The mean age of the first hypospadias repair during our study was 2.4 years, and increased postoperative complications were not observed in regard to age. Most literature has stated that younger patients who undergo hypospadias surgery are less likely to experience complications than older patients.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Because hypospadias impacts children psychologically and developmentally, the recommended age for surgery is 6 to 18 months. 7 The mean age of the first hypospadias repair during our study was 2.4 years, and increased postoperative complications were not observed in regard to age. Most literature has stated that younger patients who undergo hypospadias surgery are less likely to experience complications than older patients.…”
Section: Discussionmentioning
confidence: 52%
“…Most literature has stated that younger patients who undergo hypospadias surgery are less likely to experience complications than older patients. Dal et al 7 found that patients older than two years were more prone to postoperative complications than younger patients. A retrospective study performed in China that included fifteen medical centres and patients with a mean age of 2.9 years found no significant correlation between age at the time of surgery and complications.…”
Section: Discussionmentioning
confidence: 99%
“…Our current study supports this recommendation, with the added finding that children over 2 years of age are at increased risk of 30‐day post‐operative complications. Indeed, this finding may be explained by various factors, including the increased physical activity in children over 2 years of age, the poor compliance with prescribed medication (notably oxybutynin and laxatives), and the greater severity of stent‐associated symptoms in older children, which often leads to inappropriate handling of stents 7 …”
Section: Early Complications (N = 27) No Early Complications (N = 388...mentioning
confidence: 99%
“…Indeed, this finding may be explained by various factors, including the increased physical activity in children over 2 years of age, the poor compliance with prescribed medication (notably oxybutynin and laxatives), and the greater severity of stent-associated symptoms in older children, which often leads to inappropriate handling of stents. 7 Based on these data, we recently launched a campaign to raise awareness among primary care physicians and the public at large about the importance of seeking care from a pediatric urologist as soon as possible after the diagnosis of hypospadias. We suggest that distal hypospadias should be repaired at an early age.…”
mentioning
confidence: 99%
“…Different surgeons have different preferences as to when the optimal time for surgical correction of this anomaly is, but most agree that it is between the sixth and eighteenth month of life. This consensus has been reached by attempting to balance factors such as age-related genital dimensions and anesthetic risks, as well as the effects of toilet training and the potential psychological consequences of delaying surgery until an age when the child is genitally aware and remembers the procedure [ 5 , 6 , 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%